Analisa keterkaitan konfigurasi spasial gated community Citraland Surabaya dengan Segregasi Sosial - Salmina Wati Ginting; Vincentius Totok Noerwasito; Eko Budi Santoso (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2022)
Previous studies have shown that gated community development encourages social segregation, which occurs due to the ability of the design elements to separate from their environment. An example is the plurality of the entrance element, the provision of portals to roads, and the inaccessibility of open spaces such as parks to the public. Therefore, this study discusses the relationship between the spatial configuration of a gated community and social segregation by analyzing spatial elements, such as boundaries, roads, and public spaces. The relationship is described quantitatively with the integration value (R), both on local (R3) and global (Rn) scales, generated by the DepthmapX application from Space Syntax. One of the gated communities in Surabaya, Indonesia, Citraland, was chosen as a case study. The results showed that the higher the integration value, the lower the level of segregation and vice versa. Furthermore, it proves that the primary circulation path has the highest integration value and is the main axis influencing segregation. The number of entrances does not affect segregation as opposed to its relationship to the main axis. The number of public spaces also does not affect segregation, as opposed to the relationship between the location of public spaces and the main axis. The level of segregation of gated communities is very likely to differ on a local scale (R3) and a global scale (Rn). Citraland has proven to be integrative on a local scale but segregative on a global scale.